2004
DOI: 10.1249/01.mss.0000145467.79916.46
|View full text |Cite
|
Sign up to set email alerts
|

Model Prediction of Anterior Cruciate Ligament Force during Drop-Landings

Abstract: The pattern of ACL force in drop-landing cannot be explained by the anterior pull of the quadriceps force alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
191
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(215 citation statements)
references
References 31 publications
20
191
4
Order By: Relevance
“…A large posterior tibial slope for example, viewed to occur more frequently in women (Brandon et al, 2006), will likely promote increases in anteriorly directed tibial loads, and further orient the ACL such that a greater portion of this load is transferred along the ligament (Li et al, 2006;Petersen and Zantop, 2007). Expanding cur rent models to incorporate an anatomically relevant knee joint (Pflum et al, 2004;Shelburne et al, 2004) capable of accommodating subject-based variations in knee anato mies and laxities would provide immediate insights into individual predispositions to ACL injury based on joint and tissue biomechanical vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…A large posterior tibial slope for example, viewed to occur more frequently in women (Brandon et al, 2006), will likely promote increases in anteriorly directed tibial loads, and further orient the ACL such that a greater portion of this load is transferred along the ligament (Li et al, 2006;Petersen and Zantop, 2007). Expanding cur rent models to incorporate an anatomically relevant knee joint (Pflum et al, 2004;Shelburne et al, 2004) capable of accommodating subject-based variations in knee anato mies and laxities would provide immediate insights into individual predispositions to ACL injury based on joint and tissue biomechanical vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the direction of peak GRF relative to the tibia in the sagittal plane has been reported to substantially affect the amount of net proximal tibial anterior shear forces immediately after the foot contact of landing. 11,12 In their video analysis, Krosshaug et al 15 estimated that noncontact ACL injuries occurred approximately 40 milliseconds after foot contact during landing or cutting, which closely corresponds to the time to peak GRF during single-legged landing. 16 The results of these studies collectively have indicated that sagittal-plane mechanics, including GRF direction and magnitude and sagittal-plane knee kinetics and kinematics, may greatly affect the direction and magnitude of peak tibiofemoral forces, influencing ACL loading immediately after foot contact during sharp decelerating motions.…”
mentioning
confidence: 99%
“…4,8 Proximal tibial anterior shear forces are thought to be the primary cause of ACL injury because they directly load the ACL, especially at shallow knee-flexion angles. 3,9 Investigators [10][11][12] have shown that the ground reaction forces (GRFs) that athletes incur right after foot contact in sharp decelerating motions greatly affect the magnitude of proximal tibial anterior shear forces and ACL loading. Authors 13,14 of in vivo studies who measured the amount of ACL strain during landing tasks demonstrated that the timing of peak ACL strain coincides with the peak GRF that occurs immediately after the foot contact of landing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Recently, computer simulations of ACL loading mechanisms have enhanced our understanding of the loading combination most likely to facilitate an ACL injury mechanism. [8][9][10][11][12][13] Even though cadaver-based and computer-simulation-based research has greatly improved our understanding of ACL injury mechanisms, this research does not identify prospective risk factors. Thus, we still have a very limited understanding of prospective risk factors for ACL injury because injury mechanisms and prospective risk factors, although related, are not identical.…”
mentioning
confidence: 99%